Curcumin-Based Nanoparticles: Advancements and Challenges in Tumor Therapy - Hicham Wahnou; Riad El Kebbaj; Bertrand Liagre; Vincent Sol; Youness Limami; Raphaël Emmanuel Duval (Pharmaceutics)
Curcumin, a bioactive compound derived from the rhizome of Curcuma longa L., has garnered significant attention for its potent anticancer properties. Despite its promising therapeutic potential, its poor bioavailability, rapid metabolism, and low water solubility hinder curcumin’s clinical application. Nanotechnology offers a viable solution to these challenges by enabling the development of curcumin-based nanoparticles (CNPs) that enhance its bioavailability and therapeutic efficacy. This review provides a comprehensive overview of the recent advancements in the design and synthesis of CNPs for cancer therapy. We discuss various NP formulations, including polymeric, lipid-based, and inorganic nanoparticles, highlighting their role in improving curcumin’s pharmacokinetic and pharmacodynamic profiles. The mechanisms by which CNPs exert anticancer effects, such as inducing apoptosis, inhibiting cell proliferation, and modulating signaling pathways, are explored in details. Furthermore, we examine the preclinical and clinical studies that have demonstrated the efficacy of CNPs in treating different types of tumors, including breast, colorectal, and pancreatic cancers. Finally, the review addresses the current challenges and future perspectives in the clinical translation of CNPs, emphasizing the need for further research to optimize their design for targeted delivery and to enhance their therapeutic outcomes. By synthesizing the latest research, this review underscores the potential of CNPs as a promising avenue for advancing cancer therapy.